How are different neural networks related to consciousness?. Issue 4 (20th August 2015) - Qin, Pengmin; Wu, Xuehai; Huang, Zirui; Duncan, Niall W.; Tang, Weijun; Wolff, Annemarie; Hu, Jin; Gao, Liang; Jin, Yi; Wu, Xing; Zhang, Jianfeng; Lu, Lu; et al.
<x xml:space="preserve">Abstract</x> Objective We aimed to investigate the roles of different resting‐state networks in predicting both the actual level of consciousness and its recovery in brain injury patients. Methods We investigated resting‐state functional connectivity within different networks in patients with varying levels of consciousness: unresponsive wakefulness syndrome (UWS; n = 56), minimally conscious state (MCS; n = 29), and patients with brain lesions but full consciousness (BL; n = 48). Considering the actual level of consciousness, we compared the strength of network connectivity among the patient groups. We then checked the presence of connections between specific regions in individual patients and calculated the frequency of this in the different patient groups. Considering the recovery of consciousness, we split the UWS group into 2 subgroups according to recovery: those who emerged from UWS (UWS‐E) and those who remained in UWS (UWS‐R). The above analyses were repeated on these 2 subgroups. Results Functional connectivity strength in salience network (SN), especially connectivity between the supragenual anterior cingulate cortex (SACC) and left anterior insula (LAI), was reduced in the unconscious state (UWS) compared to the conscious state (MCS and BL). Moreover, at the individual level, SACC‐LAI connectivity was more present in MCS than in UWS. Default‐mode network (DMN) connectivity strength, especially between the posterior cingulate cortex (PCC) and left lateral parietal cortex (LLPC), was reduced in UWS‐R compared with UWS‐E. Furthermore, PCC‐LLPC connectivity was more present in UWS‐E than in UWS‐R. Interpretation Our findings show that SN (SACC‐LAI) connectivity correlates with behavioral signs of consciousness, whereas DMN (PCC‐LLPC) connectivity instead predicts recovery of consciousness. Ann Neurol 2015;78:594–605